Auxin and Cellular Elongation - Velásquez, Silvia Melina (2016)
Auxin is a crucial growth regulator in plants. However, a comprehensive understanding of how auxin induces cell expansion is perplexing, because auxin acts in a concentration- and cell type-dependent manner. Consequently, it is desirable to focus on certain cell types to exemplify the underlying growth mechanisms. On the other hand, plant tissues display supracellular growth (beyond the level of single cells); hence, other cell types might compromise the growth of a certain tissue. Tip-growing cells do not display neighbor-induced growth constraints and, therefore, are a valuable source of information for growth-controlling mechanisms. Here, we focus on auxin-induced cellular elongation in root hairs, exposing a mechanistic view of plant growth regulation. We highlight a complex interplay between auxin metabolism and transport, steering root hair development in response to internal and external triggers. Auxin signaling modules and downstream cascades of transcription factors define a developmental program that appears rate limiting for cellular growth. With this knowledge in mind, the root hair cell is a very suitable model system in which to dissect cellular effectors required for cellular expansion.